2007
DOI: 10.1088/0953-2048/20/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Current transfer in MgB2wires with different sheath materials

Abstract: The current transfer length in composite MgB2 wires with different metallic sheaths and filament numbers was analysed. The electric potential gradient along the wire in the vicinity of the current contact was monitored as a function of transport current in various external magnetic fields up to 14 T. In all samples the characteristic current transfer length is of the order of a millimetre, varying with detailed sheath composition in the range 0.35–2 mm. For the wires with a clear reaction layer at the filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 18 publications
4
43
2
Order By: Relevance
“…Such a short current transfer length is in agreement with similar observations reported by Ekin [124]. According to the classical analytical model [130] and based on our intra-strand resistance data, the current transfer length is less than 0.1 mm.…”
Section: Measured Transfer Length In Various Samplessupporting
confidence: 92%
See 2 more Smart Citations
“…Such a short current transfer length is in agreement with similar observations reported by Ekin [124]. According to the classical analytical model [130] and based on our intra-strand resistance data, the current transfer length is less than 0.1 mm.…”
Section: Measured Transfer Length In Various Samplessupporting
confidence: 92%
“…From current transfer length measurements on Fe-sheathed MgB 2 wires [130], R was found to lie in the range ~2 to 6×10 11 Ωm 2 , which is even one order of magnitude higher than our results. For BSCCO, a range is given for R .…”
Section: Filament-to-matrix Contact Resistivity In Mgb 2 Bscco and contrasting
confidence: 75%
See 1 more Smart Citation
“…In several studies, the contact resistance has been found to be significant for MgB 2 wires and to strongly vary between samples with different matrices [19][20][21]. In addition to the losses appearing in the metal matrix, the coupling currents influence the hysteresis losses.…”
Section: Coupling Currentsmentioning
confidence: 99%
“…Several methods were developed to assess the inter-filament transverse resistance, such as measurements of the self-field distribution [4], [5]; of the AC coupling losses at low frequency [3], [6], [7]; and of the current transfer length [8]. However, the outcome of these indirect measurement methods depends on sample shape, internal wire structure, outer copper shell, Cu/nonCu ratio and twist pitch [9].…”
mentioning
confidence: 99%